APLIKASI METODE PORCINE DETECTION KIT DAN POLYMERASE CHAIN REACTION (SIMPLEKS DAN MULTIPLEKS PCR) UNTUK DETEKSI DNA SAPI, AYAM DAN BABI PADA BAKSO - , ZULI AMANAH, Prof. Dr. Ir. Umar Santoso, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Identification the type of meat in processed meat products concern and consideration because of various factors such as health, adulteration, religion, and meat industry control. The existence of a sensitive and accurate detection became an important factor in controlling the regulation of food products. The purpose of this study is to determine the presence of non-beef meat on meatballs with Porcine Detection KIT method and multiplex Polymerase Chain Reaction (PCR) PCR method was developed to identify the type of meat in meat products that undergo processing. The sample used in this study were meatballs, fresh beef, fresh chicken meat and fresh pork. Content of pork in the meatballs detection is done by making a solution of the sample with the solvent PBS (phosphate buffered saline) followed by testing using the method of Porcine Detection KIT with the principle of protein antigens reacting with antibodies meatballs contained in the strip and the red color of the complex formed on the strip. Detection of DNA on meatballs made with isolated DNA on the sample, followed by using simplex and multiplex PCR to determine the presence of a mixture of meat other than beef in meatballs. Porcine detection KIT analysis showed that all nine of the sample (B1, B2, B3, B4, B5, B6, B7, B8, B9) does not contain components pork. Then testing using simplex and multiplex PCR method on samples with specific primers cows, pigs, and chickens provide results that there are seven samples (B1, B3, B4, B5, B6, B8 and B9) containing chicken and beef, and two samples (B2 and B7) only containing cow. The test results prove that the method Porcine Detection Kit, simplex PCR and Multiplex PCR, efficient and accurate for use in identifying the type of meat in the meatball products Key word: Porcine Detection KIT, simplex PCR, multiplex PCR, meatballs, DNA, protein, isolation, electrophoresis